A Brief view on the pediatric COVID- 19 pandemic - Subhi, Mahmood D.; Obaid, Ali Abdul Razzak; AL-Zwaini, Isam; Hussein, Mohammed Jalal (AL-Kindy College Medical Journal, 2020)
The world is currently challenging the serious effects of the pandemic of the Coronavirus disease (COVID-19) caused by severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2). Data on pediatric COVID are rare and scattered in the literature. In this article, we presented the updated knowledge on the pediatric COVID-19 from different aspects. We hope it will increase the awareness of the pediatricians and health care professionals on this pandemic.